Quad-Band Bowtie Antenna Design for Wireless Communication System Using an Accurate Equivalent Circuit Model. (22nd January 2015) - Moulay, Mohammed; Abri, Mehadji; Abri Badaoui, Hadjira
Abstract : A novel configuration of quad-band bowtie antenna suitable for wireless application is proposed based on accurate equivalent circuit model. The simple configuration and low profile nature of the proposed antenna lead to easy multifrequency operation. The proposed antenna is designed to satisfy specific bandwidth specifications for current communication systems including the Bluetooth (frequency range 2.4–2.485 GHz) and bands of the Unlicensed National Information Infrastructure (U-NII) low band (frequency range 5.15–5.35 GHz) and U-NII mid band (frequency range 5.47–5.725 GHz) and used for mobile WiMAX (frequency range 3.3–3.6 GHz). To validate the proposed equivalent circuit model, the simulation results are compared with those obtained by the moments method of Momentum software, the finite integration technique of CST Microwave studio, and the finite element method of HFSS software. An excellent agreement is achieved for all the designed antennas. The analysis of the simulated results confirms the successful design of quad-band bowtie antenna.